2022
DOI: 10.1186/s12911-022-02064-5
|View full text |Cite
|
Sign up to set email alerts
|

Usability evaluation of mHealth apps for elderly individuals: a scoping review

Abstract: Background Usability is a key factor affecting the acceptance of mobile health applications (mHealth apps) for elderly individuals, but traditional usability evaluation methods may not be suitable for use in this population because of aging barriers. The objectives of this study were to identify, explore, and summarize the current state of the literature on the usability evaluation of mHealth apps for older adults and to incorporate these methods into the appropriate evaluation stage. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 100 publications
0
15
0
Order By: Relevance
“…In current mobile health applications, physical activity is measured mainly by quantitative measures (e.g., steps, distance, duration) [ 28 , 29 , 54 ]. Similarly, in our probe, we presented users with the distance and duration of the walks.…”
Section: Discussion and Design Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In current mobile health applications, physical activity is measured mainly by quantitative measures (e.g., steps, distance, duration) [ 28 , 29 , 54 ]. Similarly, in our probe, we presented users with the distance and duration of the walks.…”
Section: Discussion and Design Recommendationsmentioning
confidence: 99%
“…As with younger adults, mobile technologies have the potential to support and enhance physical activity for older adults. However, despite the variety of products and the benefit the older population may have from mobile health technologies, their adoption rate has been relatively low, and over 43% of people aged 70 years old and above quit using mobile health technology after only 14 days [ 29 ]. According to Tajudeen et al [ 30 ], this happens due to complicated features and menus as well as interface designs that do not take into consideration the older population.…”
Section: Introductionmentioning
confidence: 99%
“…There is a need for a broader focus across the continuum of care and integration into EHR systems [24]. Other examples of technologies used by nurses in practice include mHealth apps [25], telehealth solutions [26], and applications of the Internet of Things [27], to name but a few.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, technical integration into the electronic health record (EHR) needs to be available in order to facilitate patient-centered care [21][22][23]. However, a further success factor for such apps is a high rate of usability and acceptance by the users [24][25][26][27]. A study by Raeesi et al indicated that HIV/AIDS apps often do not meet user requirements [28].…”
Section: Introductionmentioning
confidence: 99%